ANALISIS PENERAPAN GREEN HOTEL DENGAN KONSEP ZERO-WASTE DALAM OPERASIONAL DI THE WESTIN RESORT NUSA DUA, BALI - Wiraharja, I Putu Gede Satria; Adyatma, I Wayan Chandra (JURNAL BISNIS HOSPITALITI, 2024)
The idea of the zero-waste concept is an approach and application of urban waste processing systems and technology on an individual and regional scale in an integrated manner with the target of reducing the volume of waste to a minimum. The Westin Resort Nusa Dua, Bali is a family and environmentally friendly 5-star hotel. An attractive hotel for tourists with our accommodation located in the same location as the Bali International Convention Center. The green and perfectly maintained resort area offers a safe and comfortable vacation spot by the beach. The Westin Resort Nusa Dua, Bali has been committed to environmental sustainability, such as not using plastic bottles and straws in any department, organic gardens and farming, locally sourced ingredients, improving environmental performance by minimizing waste, conserving natural resources and preventing pollution and committing to reducing greenhouse gas emissions, and other initiatives, as well as a commitment to zero-waste. Based on the background that has been explained, the problem formulation in this research can be determined as follows: 1. How is the Green Hotel implemented with the zero-waste concept in operations at The Westin Resort Nusa Dua, Bali? 2. What is the impact of implementing a Green Hotel with a zero-waste concept in operations at The Westin Resort Nusa Dua, Bali? The research method used is qualitative with a qualitative descriptive research approach which aims to describe, describe and summarize various conditions, situations or variables that arise in the hotel department which is the object of research. The instrument used in this research is an instrument in the form of questions for each department which contains data and interview results related to the variables in this research. The results of this research show that overall, the implementation of the Green Hotel with the Zero-Waste concept in operations at The Westin Resort Nusa Dua has been implemented well by each department and has had a positive impact in improving service quality and environmental sustainability.